Analysis Of The Effect Of Motivation Following Training And Leadership Roles On Employee Performance Through Learning Orientation - Hanif Abdillah, Muhammad (Institut Manajemen Wiyata Indonesia, 2024)
This research analyzes the influence of innovation training motivation and leadership role to employee performance trought learning orientation. The problem of the research is fully refers to research problem: there is decreasing inclination at 2017-2019 icoming tax realization. This mean tax incoming achievement in Kantor Pelayanan Pajak Pemalang not yet optimal. A literature review is arranged based on theory and practice of motivation to clarify relationship between management practice and it influence to training motivation and employee performance. This reserch also refers to control theory at leader orientation wich impres that leadership role gives feedback to arrange some one behaviour to company goal. There is a model that have been developed and five hypothese to answer this research problem. This research use census methods. Respondent are 114 person, wich are the employee of Kantor Pelayanan Pajak Pemalang. Data analyze tools wich used Structural Equation Modeling (SEM) under AMOS 4.01 program. Model and the result from research can be accepted, and prove that the influence of training motivation and leaderhip role to learning orientation are positive and significant, training motivation and leadership role are have positive and significant influence to improve employee performance. Company mangerial implication have to be based on supervisor role at step as follow. Leadership role must be some one totally credible (open minded, intelegent). Leader have to be able to give solution to employee complains problems.